TRENDS OF HUMAN DEVELOPMENT INDEX (HDI) AND INFLATION ON ECONOMIC GROWTH IN BANGKA BELITUNG - Ismail, Vicky; Nugroho, Wendy; Liza, Liza; Raihan, Ahmad Firjatullah; Putri, Aning Kesuma (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study quantitatively analyzes the impact of the Human Development Index (HDI) and inflation on Gross Regional Domestic Product (GRDP) in Bangka Belitung Islands Province from 2019 to 2021. The region’s economy relies heavily on tin mining, yet struggles with economic stability and human development, exacerbated by the COVID-19 pandemic. Using secondary data from the Central Statistics Agency (BPS) and trend analysis, this research reveals that HDI positively influences GRDP, though its growth slowed in 2020 due to pandemic-related disruptions in education and health services. Inflation exhibits a complex relationship: low inflation in 2020, driven by reduced demand, negatively affected GRDP, while the 2021 economic recovery saw inflation rise alongside GRDP growth. The novelty of this study lies in its focus on a resource-dependent region during a global crisis, highlighting how macroeconomic and human development factors interact under external shocks. Additionally, it provides empirical evidence on the dual role of inflation in economic contraction and recovery phases. Contributions include policy recommendations for stabilizing HDI growth through education and healthcare investments, as well as inflation control measures to sustain economic recovery. The study also advocates for economic diversification and infrastructure development to reduce dependency on mining and promote inclusive, long-term growth. These findings are particularly relevant for policymakers in resource-rich regions facing similar developmental challenges.